Gene-specific formation and repair of DNA monoadducts and interstrand cross-links after therapeutic exposure to nitrogen mustards - Souliotis, V.L.; Dimopoulos, M.A.; Sfikakis, P.P. (Clinical Cancer Research, 2003)
Purpose: To investigate the possibility of measuring the gene-specific DNA damage after therapeutic exposure to nitrogen mustards and to examine its relationship with the clinical response. Experimental Design: The kinetics of gene-specific monoadducts and interstrand cross-link formation/repair were measured in the p53 and N-ras genes. DNA extracted from human peripheral lymphocytes following in vitro exposure to melphalan or therapeutic exposure to melphalan or cyclophosphamide was used. Results: When lymphocytes were treated in vitro with biologically relevant doses of melphalan, monoadducts accumulated rapidly in both p53 and N-ras genes, reaching maximal levels within 2 h, whereas the highest interstrand cross-link levels were found within 8 h. Thereafter, the adducts were repaired with half-lives of 14.5 ± 0.3 h (p53) or 18.8 ± 1.5 h (N-ras) for monoadducts and 12.4 ± 0.8 h (p53) or 14.1 ± 2.2 h (N-ras) for interstrand cross-links. Moreover, peak levels of monoadducts in both genes were observed 2 h after treatment in peripheral leukocytes from patients with multiple myeloma treated with high-dose i.v. melphalan, supported by autologous stem cell transplantation, whereas interstrand cross-links were maximal within 8 h. Of seven patients examined, the three who showed the least levels of DNA damage did not respond to the high-dose melphalan. Conclusions: This is the first report showing that it is feasible to measure gene-specific DNA damage in a readily accessible tissue of humans exposed to bifunctional alkylating drugs and to examine, at the level of the individual patient, the relationships between the induction/repair of cytotoxic DNA damage and clinical response or long-term complications.